Nutrition Composition and Digestibility of Corn Straw Silage Added Leucaena and Molasses Fermented at Different Times - Oscar Yanuarianto; Muhamad Amin; Sofyan Damrah Hasan; Syamsul Hidayat Dilaga; Suhubdy Suhubdy (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2020)
The study that aimed to determine the content of crude protein (CP), crude fiber (CF) and in vitro digestibility of dry matter (DM) and organic matter (OM) of corn straw silage added with leucaena and molasses fermented at different times, had been carried out at Nutrition and Feed Laboratory, Faculty of Animal Husbandry, University of Mataram. The corn straw and leucana used in this study were taken from the agricultural area in the Gerung sub-district of West Lombok Regency shortly after harvesting and were cut into pieces with a size of 3-5 cm. This study used a Completely Randomized Design (CRD) consisting of 5 level of treatments, namely: T1: corn straw + leucaena 10% and molasses 5% without fermentation, T2: corn straw + leucaena 10% and molasses 5% fermented 7 days, T3: corn straw + leucaena 10% and molasses 5% fermented 14 days, T4: corn straw + leucaena 10% and molasses 5% fermented 21 days, T5: corn straw + leucaena 10% and molasses 10% fermented 28 days. The variables observed in this study were CP, CF, and in vitro digestibility of DM and OM. Data obtained in this study were analyzed using analysis of variance based on a Completely Randomized Design using the SAS statistical program package and the differences were further tested using the Duncan Test. The results showed that fermentation time could significantly decrease (P <0.05) CF content and increase (P <0.05) CP silage content, but there was no significant increase (P> 0.05) of DM and OM digestibility in vitro of silage fermented for 7, 14, 21 and 28 days.